Antitumor activity of miR-34a in peritoneal mesothelioma relies on c-MET and AXL inhibition: persistent activation of ERK and AKT signaling as a possible cytoprotective mechanism. Issue 1 (December 2017) - El Bezawy, Rihan; De Cesare, Michelandrea; Pennati, Marzia; Deraco, Marcello; Gandellini, Paolo; Zuco, Valentina; Zaffaroni, Nadia
Abstract Background The value of microRNAs (miRNAs) as novel targets for cancer therapy is now widely recognized. However, no information is currently available on the expression/functional role of miRNAs in diffuse malignant peritoneal mesothelioma (DMPM), a rapidly lethal disease, poorly responsive to conventional treatments, for which the development of new therapeutic strategies is urgently needed. Here, we evaluated the expression and biological effects of miR-34a—one of the most widely deregulated miRNAs in cancer and for which a lipid-formulated mimic is already clinically available—in a large cohort of DMPM clinical samples and a unique collection of in house-developed preclinical models, with the aim to assess the potential of a miR-34a-based approach for disease treatment. Methods miR-34a expression was determined by qRT-PCR in 45 DMPM and 7 normal peritoneum specimens as well as in 5 DMPM cell lines. Following transfection with miR-34a mimic, the effects on DMPM cell phenotype, in terms of proliferative potential, apoptotic rate, invasion ability, and cell cycle distribution, were assessed. In addition, three subcutaneous and orthotopic DMPM xenograft models were used to examine the effect of miR-34a on tumorigenicity. The expression of miRNA targets and the activation status of relevant pathways were investigated by western blot. Results miR-34a was found to be down-regulated in DMPM clinical specimens and cell lines compared to normal peritoneal samples. miR-34a reconstitution in DMPM cells significantly inhibited proliferation and tumorigenicity, induced an apoptotic response, and declined invasion ability, mainly through the down-regulation of c-MET and AXL and the interference with the activation of downstream signaling. Interestingly, a persistent activation of ERK1/2 and AKT in miR-34a-reconstituted cells was found to counteract the antiproliferative and proapoptotic effects of miRNA, yet not affecting its anti-invasive activity. Conclusions Our preclinical data showing impressive inhibitory effects induced by miR-34a on DMPM cell proliferation, invasion, and growth in immunodeficient mice strongly suggest the potential clinical utility of a miR-34a-replacement therapy for the treatment of such a still incurable disease. On the other hand, we provide the first evidence of a potential cytoprotective/resistance mechanism that may arise towards miRNA-based therapies through the persistent activation of RTK downstream signaling.